Endodontic Surgery of the Palatal Root of a Maxillary Molar Associated with Simultaneous Management of a Maxillary Sinus Lesion - Silvio Taschieri; Stefano Corbella; Luca Francetti; Alice Alberti; Benedetta Morandi (Case Reports in Dentistry)
This case report describes a particular application of endodontic microsurgery with a palatal approach in the presence of a radiopaque lesion inside the maxillary sinus. The patient presented complaining of pain related to the first maxillary molar and events of nasal obstruction and facial pain in the cheek and nasal area. The endodontic orthograde treatment and retreatment were done, respectively, 7 and 4 years earlier. The cone-beam computed tomography (CBCT) scan taken before the treatment showed two separate lesions: one associated with the palatine root of the molar and another one inside the maxillary sinus. The patient agreed to solve both problems in one surgical step: endodontic surgery of the palatine root with palatal access with the simultaneous asportation of a lesion from the maxillary sinus floor. Complete bone healing of the periapical area and the maxillary sinus was visualized on intra-oral radiographs, and CBCT was taken one year after the treatment. As far as the authors know, no one in literature has ever described this approach and solved in such a conservative way both the problems at the tooth and in the maxillary sinus.